2020
DOI: 10.25259/sni_5_2020
|View full text |Cite
|
Sign up to set email alerts
|

Precision of preoperative diagnosis in patients with brain tumor – A prospective study based on “top three list” of differential diagnosis for 1061 patients

Abstract: Background: Accurate diagnosis of brain tumor is crucial for adequate surgical strategy. Our institution follows a comprehensive preoperative evaluation based on clinical and imaging information. Methods: To assess the precision of preoperative diagnosis, we compared the “top three list” of differential diagnosis (the first, second, and third diagnoses according to the WHO 2007 classification including grading) of 1061 brain tumors, prospectively and consecutively registered in preoperative case conferences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“… 6 Nevertheless, the enhancing patterns on imaging exhibit a high degree of similarity across these tumor types, making differential diagnosis challenging even for experienced neuroradiologists. 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“… 6 Nevertheless, the enhancing patterns on imaging exhibit a high degree of similarity across these tumor types, making differential diagnosis challenging even for experienced neuroradiologists. 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…Categorization can, in turn, be split into diagnosis and prognosis. In diagnosis, the correlation between neuroimaging classifications and histopathological diagnoses was assessed in [12] based on the 2000 version of the WHO classification of brain tumors and in [13] based on the 2007 version. In both studies, the main finding was that the sensitivity was variable among classes, whereas specificity was in the range of 0.85-1.…”
Section: Open Problems In Ai Applied To Mri Analysismentioning
confidence: 99%
“…The study based on the 2000 classification [12] reported a sensitivity of 0.14 for low-grade astrocytoma and 0.15 for low-grade oligodendroglioma. In the study based on the 2007 classification [13], increased sensitivity for low-grade astrocytoma (0.56) was found, but sensitivity was still low for other low-grade gliomas (LGG) such as oligodendroglioma (0.26), or for anaplastic gliomas (astrocytoma, 0.17 or ependymoma, 0.00), and other classes in the long-tail such as meningiomas of grade II and III in aggregate (0.17), or subependymomas and choroid plexus papilloma (0.33 for both). The recently released 2021 WHO classification [14], which incorporates the genetic alterations, opens the door to the reevaluation of these baseline results to accurately estimate the added value of any clinical decision support system (CDSS) based on ML or radiogenomics, over the limits of radiological interpretation of imaging findings.…”
Section: Open Problems In Ai Applied To Mri Analysismentioning
confidence: 99%
“…Therefore, to accurately identify normal or abnormal features of MRI scans, it is not reliable to rely on the evaluation of medical professionals [3,4]. Doctors are unable to prescribe drugs accurately based on an inaccurate diagnosis, and as a result the patient's chances of survival are reduced [5]. The diagnosis was confirmed by pathological confirmation of a biopsy or surgical resection.…”
Section: Introductionmentioning
confidence: 99%